Exploring the long-term impact of development interventions within life-history narratives in rural Bangladesh - Davis, Peter (International Food Policy Research Institute, 2010)
This paper explores the long-term effects of a set of development interventions within the life trajectories of people in rural Bangladesh, using findings from 293 life-history interviews and an accompanying set of focus group discussions conducted in 2007. The paper uses various methods to address the challenge of assessing the long-term impact of development interventions. It then goes on to discuss what was learned about the impact of microfinance, educational transfer, and agricultural technology development programs from the life-history narratives. The life-history interviews show that microfinance services are now widespread in rural Bangladesh, with 55 percent of research participants having used these services for some kind of income-generating activity at some time. Microfinance contributed to at least one of the three or four most important causes of well-being improvement within the life trajectories in 18 percent of research participants. However, 37 percent of research participants used microcredit to cope with crises or to maintain consumption, rather than to generate income. Educational transfers, such as food for education and cash for education, were also viewed positively by research participants and were seen as contributing positively in the life histories of 29 percent of participants. However, educational transfers were listed as a main cause of life improvement for only 7 percent of participants.